Electroanalytical application of screen-printed carbon electrode modified with conductive graphene oxide-poly(acrylic acid) film for label-free detection of human immunoglobulin G - Norfun P. (2017)
© 2016 The Chemical Society of Japan. A facile and cost-effective modification of screen-printed carbon electrode employing a graphene oxide-poly(acrylic acid) film allows both good electrochemical reactivity and electrode surface functionalization with antibody. The analytical performances of the modified electrode for detection of human immunoglobulin G (IgG) were satisfied with a linear concentration range of 1.0-100 ng mL -1 , sensitivity of 1.2318 μA cm -2 mL ng -1 , and a limit of detection of 0.54 ng mL -1 . The proposed electrode is promising in sensitive and selective clinical analysis to detect IgG at physiological concentration.